PRESERVICE TEACHERS’ TECHNIQUES FOR GENERATING NEW PROBLEMS - Fardah, Dini Kinanti (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
Evaluating students’ achievement is one significant part of teachers’ pedagogical competency. However, teachers should give problems in vary to their students. The ability of the teachers in developing the new problem from the existing or available problems is necessary to be mastered. This paper aimed to analyze preservice teachers’ techniques in developing new problems. Twenty-nine preservice teachers who had experience in internship program were given three mathematical problems each in probability, trigonometry and number and pattern. They were asked to generate new problems from those problems given. The techniques used by the teachers on generating new problems from the original problems were analyzed and classified as replacement, addition, modification, contextualizing the problem, turning around the problem, and reformulation technique. In summary, teachers are most frequently taking the same given information but changing the problem from the old one. Teachers were still unfamiliar to turn the problem around by taking the end goal as given and the given as the end goal. The implication of this study is lecturers of mathematics education program especially in the subject that contains assessment and evaluation need to consider about developing the preservice teachers’ ability to generate new problems from the old or existing problem given in all types of the development.